Entrepreneurship in Islamic Education Institutions: Pesantren Strategy in Responding to the Industrial Revolution 4.0 - Rouf, Abdur; Syukur, Fatah; Maarif, Samsul (Tafkir: Interdisciplinary Journal of Islamic Education, 2024)
This study aims to explore the proactive steps of pesantren in improving the entrepreneurial skills of Santri to respond to the Industrial Revolution 4.0. The study, which was conducted at Pesantren Al-Mawadah Honggo Suco Kudus, used a case study approach with data collection techniques through observation, interviews, and document analysis. The collected data were analyzed using a qualitative approach with thematic analysis techniques. The results showed that Pesantren Al-Mawadah Honggo Suco Kudus has four excellent programs to support these goals. First, through training and workshops that focus on developing digital skills such as programming, graphic design, and social media management. Second, by strengthening technology-based education through curriculum relevant to Industry 4.0, such as artificial intelligence, data analysis, and the Internet of Things (IoT). Third, through collaboration with related companies and institutions to provide access to pesantren and students in understanding the latest industry needs and building networks that are useful in the business world. Fourth, by applying an experiential learning-oriented learning approach to teach students how to think creatively, innovatively, and adaptively. The challenges faced are the lack of understanding of entrepreneurial concepts and practices among pesantren teachers and managers as well as access to resources and capital to develop entrepreneurial activities. This research provides a foundation for the development of an entrepreneurship curriculum that is relevant and useful for Santri in welcoming industry 4.0.